Avaliação nutricional do farelo de girassol na alimentação de frangos de corte - Oliveira, Taciana Maria Moraes de (2013)
By means of conducting this research, have aimed to evaluate the inclusion of sunflower meal (SFM) as feed for broilers. The chemical composition and energetic values of SFM were obtained by the total excreta collection method using male broilers, at growing age, distributed in a completely randomized design with four treatments and four replicates (10, 20, 30 and 40% replacement of SFM in a reference diet). To determine the SFM total and digestible amino acids profile and evaluate changes in the determination of true digestible amino acids methodology, another experiment was conducted employing the technique of forced feeding using cecectomized roosters allotted in three treatments with six replicates. The treatments consisted in: T1 - provide 30 g of SFM divided in two intubations of 15 g at interval of 12 hours (control), T2 - 30 g of SFM divided in two intubations of 15 g at intervals of 24 hours and T3 - 15 g of SFM provided in a single intubation, beeing the obtained data at T1 also employed for the determination of digestible amino acids. To evaluate the performance, intestinal morphometry and carcass yield of broilers fed with diets containing SFM, supplemented or not with enzymes besides the economic viability of SFM inclusion, two trials were consucted. At first, 1100 male broiler chicks 1-d old, Cobb, were distributed in a completely randomized design in a 2x5 factorial arrangement, consisting of the combination of the factors addition of multienzyme complex or not and five inclusion levels of SFM (0, 4, 8, 12 and 16%). The test-food was supplied only up to 21-d and lately, all birds were fed with same diet up to 42-d, with the aim of evaluating the possible residual effect of the treatments. At second trial, 750 male broilers 1-d old, Cobb, were used and distributed in the same way as the first experiment, however, the birds were treated from 21 up to 42-d old. The determined chemical composition was: 89.51% of dry matter, 36.46% of crude protein, 4294 kcal.kg-1 of gross energy, 1.31% of crude fat, 6.15% of mineral matter, 1.15% of phosphorus, 0.33% of calcium; 35.32% of neutral detergent fiber, 22.30% of acid detergent fiber and 1418 kcal.kg-1 of metabolizable energy, The amino acids digestibility coefficient of SFM was influenced by methodology used in its determination in relation to inclusion level to lysine, methionine, threonine, arginine, leucine and isoleucine. The birds performance at 21-d old was affected by dietary inclusion of SFM and the supplementation with multienzyme complex improved the parameters that exerted significant. The duodenum and ileum villus height and jejunum crypt depth were affected by the inclusion of SFM and the variables presented larger values due to the presence of enzymes in the diet. For broilers that received SFM from 21-d old, supplementation with multienzyme complex decreased consumption, carcass yield and breast decreased linearly with SFM inclusion and for the gizzard was observed significant interaction between inclusion level of SFM and enzyme addition. The inclusion level of SFM influenced the duodenum and jejunum villus height and enzymes affect the ileum. The duodenum crypt depth showed interaction between SFM inclusion and enzyme addition. The villus height:crypt depth ratio was affected in all segments by inclusion level of SFM and enzyme addition, but only in the duodenum was significant interaction